Weed cover unaffected after converting a dairy farm to organic production - Harrington, K.C.; Osborne, M.A.; Kemp, P.D. (New Zealand Plant Protection, 2008)
One half of a Massey University dairy farm was converted to an organic production system in 2001 and the other half continued to be farmed as a conventional unit Aspects of these two systems have been compared over the subsequent years including the weed flora measured twice a year since 2003 along set transects within each system Overall there has been no significant increase in the weed cover of the organic pastures during the 4 years since measurements began With both systems pasture weediness increased mainly after new pastures were established Although selective herbicides could be used in the conventional system to reduce this weediness the weed content quickly decreased to tolerable levels in the organic system through grazing management Hairy buttercup (Ranunculus sardous) and broadleaved dock (Rumex obtusifolius) were the two dominant species in both systems and factors that influenced which species dominated are discussed